Dephasing optimization through coherence order pathway selection (DOTCOPS) for improved crusher schemes in MR spectroscopy. Issue 4 (3rd November 2018) - Landheer, Karl; Juchem, Christoph
Abstract : Purpose: To develop an algorithm which can robustly eliminate all unwanted coherence pathways for an arbitrary magnetic resonance spectroscopy experiment through the adjustment of the relative amplitudes of crusher gradients, thereby reducing the effects of spurious echoes and mislocalization. Theory and Methods: The effect of crushing gradients for all coherence pathways was modeled according to the associated physics, and a cost function was optimized which maximally crushes all unwanted coherence pathways, while unaffecting the desired coherence pathway(s). The efficacy of the method was tested versus literature schemes from 2 separate MR spectroscopy (MRS) sequences: sLASER and MEGA‐sLASER with both phantom and in vivo experiments. Results: Improved crushing power for 2 separate MRS sequences was demonstrated for 2 crushing schemes adopted from the literature in both phantom and in vivo data. Conclusion: A novel algorithm and associated software was developed based on rigorous treatment of all coherence pathways, which can be applied to any arbitrary magnetic resonance spectroscopic pulse sequence of interest and any arbitrary coupled spin system. This developed method solves a long‐standing problem in in vivo MRS and is expected to critically improve the data quality of virtually all MRS applications.